Al-Farabi's Political Ethics and Democratic Practices in Indonesia: A Study of Regional Election - Sahroni Nasution (Islamic Thought Review, 2025)
This study explores the relevance of Al-Farabi’s political ethics in the practice of democracy in Indonesia, with a specific focus on regional elections as a manifestation of people’s sovereignty. Indonesia, as a democratic republic, grants its citizens the right to directly elect their leaders, reflecting the principles of political participation. However, in practice, regional elections are often marred by various problems such as money politics, negative campaigning, vote manipulation, and the rise of identity politics, which contradict the ideals of political ethics. Using a qualitative library research method with a philosophical approach, this study examines Al-Farabi’s ideas on political ethics and their application to contemporary democratic practices. The findings reveal that, first, Al-Farabi emphasizes that the foundation of political ethics lies in the ultimate goal of human life, namely happiness; second, political ethics serve as a means to achieve collective happiness as well as a moral compass for leadership; and third, the application of political ethics in Indonesia’s regional elections remains incomplete due to persistent ethical violations. This research underscores the importance of revisiting classical political thought as a normative framework for strengthening democracy and promoting ethical leadership in Indonesia.